2019
DOI: 10.21744/ijllc.v5n2.605
|View full text |Cite
|
Sign up to set email alerts
|

Grammatical errors of writing in EFL class

Abstract: The current paper is descriptive qualitative research which aimed at describing grammatical errors of students’ writing in English as a Foreign Language (EFL) Class. Data were gained from documents written by students of State Polytechnic in Kupang City, East Nusa Tenggara- Indonesia. The results have shown that the highest percentage of grammatical errors occurred in using the verb group. It consisted of 65.0 %. Following these errors, students made errors in the use of prepositions (12.8 %). The third errors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
(14 reference statements)
0
14
0
Order By: Relevance
“…Based on the results of data analysis, it can be concluded that the application of the principle of cooperation in interaction with Indonesian language learning in class X of SMAN 1 Tampaksiring includes adherence to the principle of cooperation. In the application, the principle of cooperation found and dominated by 3 maxims out of 4 maxims (as proposed by Grice (1975), namely the quality maxim, quantity maxim, and method maxim). Speech (1) until speech (3) was an embodiment of the principle of cooperation so that the learning process can run efficiently and effectively.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of data analysis, it can be concluded that the application of the principle of cooperation in interaction with Indonesian language learning in class X of SMAN 1 Tampaksiring includes adherence to the principle of cooperation. In the application, the principle of cooperation found and dominated by 3 maxims out of 4 maxims (as proposed by Grice (1975), namely the quality maxim, quantity maxim, and method maxim). Speech (1) until speech (3) was an embodiment of the principle of cooperation so that the learning process can run efficiently and effectively.…”
Section: Resultsmentioning
confidence: 99%
“…Language as a communication tool is used by teachers and students in a classroom and is presented during the teaching and learning process (Latupeirissa & Sayd, 2019). Good teacher competence is needed to build the interaction of educators and students and improve the competence of educators in the learning process should be able to create learning activities in an interactive, inspiring, fun, challenging, motivating learners to participate actively, contextually and collaboratively, giving enough space to stimulate creativity and independence of students, and in accordance with the talents, interests, abilities, and physical and psychological development of students.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the process of changing time and space as well as historical, political, cultural, social events, etc., probably make the initial objective and subjective reasons of the intended subject unclear. Therefore, to understand the reasons for naming Ede words of social relations, we can study the original language science (Latupeirissa & Sayd, 2019;Sujaya & Sukiani, 2020).…”
Section: Nouns Of Social Relationsmentioning
confidence: 99%